Internationalization of Business Cases on Strategy Formulation and Implementation (MIR Series in International Business, 2018)
This book illustrates the various facets of internationalization in managerial practice, starting with a strategic outline of the many options firms have when formulating internationalization strategies. Designed as a textbook for Bachelor, Master and MBA classrooms, the core of the book consists of six case studies on firms from diverse industries, such as sporting goods, aviation, grocery discount, motorcycle, computer and IT, and fast-food. The cases present a variety of ways of entering and operating in foreign markets, such as export, franchising, joint ventures, strategic alliances, greenfield-investments, acquisitions and mergers. In addition to market entry strategies, the cases provide readers, educators and students with insights into target market strategies, timing strategies, allocation strategies and coordination strategies of well-known companies.